Evaluasi Kemampuan Fisik Pengangkatan Secara Manual Berdasarkan Pedoman NIOSH - Yusuf, Muhammad; Regina Nansi, Maria; Maulana, Rian; Amal, Ichlasul (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2023)
Manual lifting activities are still often used in the industrial world, both small and large industries. Occupational safety and health need to be considered because things caused by errors in material handling and excessive loads can cause injuries. This research was carried out in roof tile making activities in Godean. The activities carried out still use human power in flowing materials with the process flow. If this activity is carried out continuously, it is feared that it will cause accidents. Therefore, there is a need for evaluation, namely energy consumption by measuring heart rate, determining optimal rest time, Recommended Weight Limit (RWL) is a recommendation for the limit of weight that can be lifted by humans without causing injury even if done repetitively and over a long period of time. This RWL is determined by NIOSH (National Institute for Occupational Safety and Health) and the Job Severity Index (JSI). This research is useful for providing information and input about the importance of health and safety as well as providing information and insight for workers to pay more attention to occupational health and safety.